Measuring connectedness of euro area sovereign risk - Rebekka Buse; Melanie Schienle (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2019)
We introduce a method for measuring default risk connectedness of euro zone sovereign states using credit default swap (CDS) and bond data. The connectedness measure is based on an out-of-sample variance decomposition of model forecast errors. Due to its predictive nature, it can respond more quickly to crisis occurrences than common in-sample techniques. We determine sovereign default risk connectedness with both CDS and bond data for a more comprehensive picture of the system. We find evidence that several observable factors drive the difference of CDS and bonds, but both data sources still contain specific information for connectedness spill-overs. Generally, we can identify countries that impose risk on the system and the respective spill-over channels. In our empirical analysis we cover the years 2009-2014, such that recovery paths of countries exiting EU and IMF financial assistance schemes and responses to the ECB's unconventional policy measures can be analyzed.
urn:nbn:de:swb:90-924708
Keywords: C58; G01; G15; C32; 330; Variance decomposition; Sovereign risk; Connectedness; Credit default swaps; Bonds; Eurozone crisis